Liquisolid systems: From formulation development challenges to improved bioavailability - Aleksić, Ivana (Archives of Pharmacy, 2022)
Increasing number of poorly water-soluble drugs poses the great challenges in formulation development of solid dosage forms. To overcome bioavailability issues numerous approaches have been developed during last decades. Most of the commonly applied methods are associated with the use of complex and/or energy consuming technological processes (e.g. different techniques for preparation of solid dispersions). From the late 1990s the idea of converting drug solution/suspension into dry-looking powder has evolved from “powdered solution technology” to liquisolid systems as a simpler, greener process requiring lower production costs in comparison with commonly used approaches for bioavailability enhancement. Liquisolid technology considers conversion of drug dispersion (preferably solution) in non-volatile, hydrophilic liquid vehicle into the powder that is not only free flowing, but also possess acceptable compaction properties required for tableting or capsule filling. Development of novel, highly porous excipients has further increased research interest and possibility for wider use of this technique. Numerous studies have demonstrated the potential of this emerging technique to enhance in vitro dissolution rate, and some studies have also confirmed improved bioavailability of various poorly water-soluble drugs from liquisolid formulations. Furthermore, this promising technique has been investigated as an approach to prepare orally disintegrating tablets, modified release preparations, as well as solid dosage forms with liquid herbal extracts. Recent studies address the lack of knowledge regarding compaction behavior of these systems and the need for new solutions to overcome limitations related to application of this technology in the case of high-dose drugs.